Motivation And Competency Factors Influencing Tutors Performance In Educational Equality Of Study Group Musi Banyuasin Regency - Desi Ulpa Anggraini; Yeni Marsih; Achmad Kartiko Buwono; Aan Ardiansyah (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
The lack of motivation and competence in the performance of tutors in the education equality of study groups in the Non-Formal Education Unit of the Musi Banyuasin Regency was the background for this research. The purpose of this study is to prove the influence of motivation and competence on the tutor's performance. The population in this study were all Group Equality Tutors, total to 70 people. Primary data used from questionnaires by respondents. Sample selection is done by simple random sampling. Data management techniques used the SPSS version 20 program and tested it using multiple linear regression equations. The results of the study simultaneously produce an R2 (R square) of 0.169 indicating the variable competence and work motivation affect tutor performance by 16.9%, and the remaining 83.1% is influenced by other variables. While partially there is an influence between motivation on performance that produces a tcount of 3.501, and there is no influence between competence on performance with the result of a tcount of 1.820.